2010
DOI: 10.1111/j.1600-0587.2010.06490.x
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous local dynamics contributes to stability of a seagrass bed in Tokyo Bay

Abstract: Abstract:It is known that asynchronous temporal variations in local populations can contribute to the stability of metapopulations. However, studies evaluating the hierarchical organization of multiple spatial scales are rare for continuous marine landscapes, especially for marine vegetation such as seagrass beds. In this study, long-term observation (26 years) of temporal changes and nested spatial analyses were combined for an extensive seagrass meadow in Tokyo Bay, Japan, using remote sensing and geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Reed and Hovel, 2006;Yamada et al, 2007a). These findings suggest that the existence and/or dynamics of patches of seagrass (e.g., Vellend and Geber, 2005;Phinn et al, 2008;Yamakita et al, 2011;Chust et al, 2013a) may affect the variation of functional groups, that is, patch dynamics may ensure the variation of ecosystem functions provided by macroinvertebrate communities. In support of this idea, Yamada et al (2011) concluded that the functional diversity of the macrocrustacean community in seagrass ecosystems is the variable at the local patch scale, but homogeneous (i.e., occurrence of functional redundancy) at the regional scale (e.g.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Reed and Hovel, 2006;Yamada et al, 2007a). These findings suggest that the existence and/or dynamics of patches of seagrass (e.g., Vellend and Geber, 2005;Phinn et al, 2008;Yamakita et al, 2011;Chust et al, 2013a) may affect the variation of functional groups, that is, patch dynamics may ensure the variation of ecosystem functions provided by macroinvertebrate communities. In support of this idea, Yamada et al (2011) concluded that the functional diversity of the macrocrustacean community in seagrass ecosystems is the variable at the local patch scale, but homogeneous (i.e., occurrence of functional redundancy) at the regional scale (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…Vellend and Geber, 2005;Phinn et al, 2008;Yamakita et al, 2011). The presence of seagrass increases habitat complexity and provides living space, shelter, and feeding and nursery grounds for a greater variety and abundance of faunal species than in adjacent unvegetated habitats (Connolly and Hindell, 2006;Horinouchi, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this could be that aggregate communities are typically probed in metanalyses of large databases. However, evidence for compensation appears strongest when assemblages are decomposed, for example, by taking account of variation in ecophysiology [33] or habitat heterogeneity [34]. Detailed local knowledge of taxa thus remains an essential part of community ecology alongside broad brush macroecological analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the classification accuracy of the images without the water column correction was better than that of the images with the water column correction. To our knowledge, however, some recent studies without water column correction for analysis of submerged vegetation have been reported (e.g., Pasqualini et al, 2005, Gullstrom et al, 2006, Phinn et al, 2008, Wabnitz et al, 2008, Yamakita et al, 2011, Roelfsema et al, 2013, and these studies without the correction were mostly done in shallow water (<10 m). The result of this study was also considered to be scientifically sufficient in terms of the reliability of the data, even though we did not use the most suitable method for the analysis of aerial images.…”
Section: Image Processingmentioning
confidence: 99%